2022
DOI: 10.3390/nano12111877
|View full text |Cite
|
Sign up to set email alerts
|

Large Enhancement in Thermal Conductivity of Solvent−Cast Expanded Graphite/Polyetherimide Composites

Abstract: We demonstrate in this work that expanded graphite (EG) can lead to a very large enhancement in thermal conductivity of polyetherimide−graphene and epoxy−graphene nanocomposites prepared via solvent casting technique. A k value of 6.6 W⋅m−1⋅K−1 is achieved for 10 wt% composition sample, representing an enhancement of ~2770% over pristine polyetherimide (k~0.23 W⋅m−1⋅K−1). This extraordinary enhancement in thermal conductivity is shown to be due to a network of continuous graphene sheets over long−length scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The composite also showed an electrical conductivity of 969 S m −1 . For the same filler concentration, Tarannum et al 104 demonstrated that the polyetherimide/EG composite exhibited 900% higher thermal conductivity (10 W m −1 K −1 ) than the polyetherimide/ graphene composite following a solvent casting process.…”
Section: Expanded Graphite Facilitated Interconnected Graphene Networkmentioning
confidence: 99%
“…The composite also showed an electrical conductivity of 969 S m −1 . For the same filler concentration, Tarannum et al 104 demonstrated that the polyetherimide/EG composite exhibited 900% higher thermal conductivity (10 W m −1 K −1 ) than the polyetherimide/ graphene composite following a solvent casting process.…”
Section: Expanded Graphite Facilitated Interconnected Graphene Networkmentioning
confidence: 99%
“…With an increase in density, the number of contacts between graphite packs increases, which leads to a regular decrease in the porosity of the material and better adhesion of particles to each other [ 34 , 35 ]. This leads to an increase in the electrical and heat-conducting properties of the material [ 36 , 37 , 38 , 39 , 40 ], while its gas permeability decreases [ 19 , 27 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In general, adding conductive nanofillers to a polymer matrix is a versatile approach to improve its thermal conductivity. 5,6 Researchers have attempted to improve the thermal conductivity of PI or PEI by adding various pure or hybrid nanofillers, such as carbon nanofibers, 7 aluminum nitride (AlN), 8 low-melting-point SnBi 17 Cu 0.5 , 9 hybrid carbon nanotube (CNT)/PI-grafted multiwall CNT/AlN, 10 PI-coated hexagonal boron nitride (h-BN), 11,12 iron oxide-doped h-BN, 12 expanded graphite, 13 short fiber/expanded graphite, 14 alkyl-or phenyl-aminated graphene oxide (GO), 15,16 graphite nanoplatelets, 17 and graphene nanoplatelets (GNPs) 18 to the polymer matrix. Among these, GNPs and their derivatives or hybrids are versatile nanofillers that have also been used to improve the thermal conductivity of other polymer matrices.…”
Section: Introductionmentioning
confidence: 99%